Potential of Ayurvedic Drugs in Differentiating Neuronal Stem Cells from Human Breast Milk: A Review - Kumari, Rinki (Nepal Journal of Biotechnology, 2019)
Recently, Stem cell therapy has revolutionized excellent clinical therapy with the potential of stem cells to differentiate into various cell types and it may help to replace different cell lines of an organism. Frequent, clinical trials are carried out to merge the new scientific stem cell information and techniques with traditional knowledge and plant extracts that may result in less toxic, affordable, and highly available natural alternative therapeutics. Ayurveda, the traditional Indian system of medicine has given great emphasis to the promotion of health. Ayurveda therapies are based on the restoration of body balance and nourishment of dhatus. Rasayana concept of Ayurveda explains tissue regeneration and cell renewal. Rasayana drugs and therapies provide research opportunities for the biology of regeneration. Specific Medhya Rasayana stimulates and nourishes respective Medha (Dhi, Driti, and Smriti) dhatus. Interpretation of this description offers clues for specific differentiation of neuronal stem cells from human breast milk (HBM) in the presence of some herbal extracts. The previous studies suggest that neuronal stem cells differentiate from Human Breast Milk (Human mesenchymal stem cell) more effectively with Madhya Rasayana drugs.The present review highlights the potential of Ayurveda and its possible contributions in regenerative medicine.